2021
DOI: 10.3390/met11091437
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a New SEN Design with an Inner Flow Divider

Abstract: To minimize the product imperfections due to slag entrapment and surface defects, the fluid flow pattern inside the mold must be symmetric, commonly named double-roll flow. Thus, the liquid steel must enter into the mold evenly distributed. The submerged entry nozzle (SEN) is crucial in product quality in vertical steel slab continuous casting machines because it distributes the molten steel from the tundish into the mold. This work evaluates the performance of a novel bifurcated nozzle design named “SEN with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(39 reference statements)
4
4
0
Order By: Relevance
“…The nozzle exit-jet particularities listed previously agree with the analysis presented in Gonzalez et al [18], where the hydrodynamics inside the SEN was studied, and the effect of adding the flow divider was also evaluated. Gonzalez et al [18] showed that three different fluid flow patterns determine the hydrodynamics inside the SEN for the FB and the WB nozzles.…”
Section: Frontal Viewsupporting
confidence: 81%
See 4 more Smart Citations
“…The nozzle exit-jet particularities listed previously agree with the analysis presented in Gonzalez et al [18], where the hydrodynamics inside the SEN was studied, and the effect of adding the flow divider was also evaluated. Gonzalez et al [18] showed that three different fluid flow patterns determine the hydrodynamics inside the SEN for the FB and the WB nozzles.…”
Section: Frontal Viewsupporting
confidence: 81%
“…The nozzle exit-jet particularities listed previously agree with the analysis presented in Gonzalez et al [18], where the hydrodynamics inside the SEN was studied, and the effect of adding the flow divider was also evaluated. Gonzalez et al [18] showed that three different fluid flow patterns determine the hydrodynamics inside the SEN for the FB and the WB nozzles. One pattern is symmetric concerning a vertical plane aligned with the X-X' symmetry axis of the SEN, shown in Figure 2.…”
Section: Frontal Viewsupporting
confidence: 81%
See 3 more Smart Citations